Georgia - Report on the Observance of Standards and Codes : Corporate Governance Country Assessment - World Bank (Washington, DC: World Bank, 2022)
This report assesses the Republic of Georgia’s corporate governance (CG) policy framework, as it stands in December 2021. The report on the observance of standards and codes (ROSC) highlights recent improvements in CG regulations, assesses actual practices, makes policy recommendations, and provides investors with a benchmark against which to measure CG in Georgia. The report focuses on the governance of public interest entities (PIEs), which in Georgia are defined by law to include listed companies, banks, and state-owned enterprises (SOEs). The report draws on several sources of data, including a detailed country assessment completed by Dentons Georgia LLC, that covered both the legal framework and CG practices. Recommendations draw on a range of internationally recognized standards, guidelines, and practices, and the latest available research produced by the World Bank and others. The report also uses the policies and practices outlined in the World Bank’s integrated SOE framework (iSOEF) and toolkit on CF of SOE, for the assessment of SOE governance frameworks and practices. This report offers a comprehensive assessment of the existing CG policies and practices in Georgia, and suggests policy recommendations for consideration, which are summarized in a sequenced action plan. The report and its recommendations are tailored to the country’s context and its current development stage and reflect the recent improvements to the legal and regulatory environment.